О коррективе в тяговом усилии электромагнитного вибровозбудителя - Божко, А.Е. (Видавничий дім "Академперіодика" НАН України, 2008)
A new formula for the tractive force of an electromagnetic exciter is given. This formula takes into account a change of the air clearance on oscillations of the anchor.